An improved Burgers creep model of coal based on fractional-order - Yang, Yongjie; Huang, Gang; Zhang, Yangqiang; Yuan, Lei (Frontiers in Earth Science, 2023)
The instability and destruction of various types of coal pillars left in deep underground mining are frequently attributed to cumulative creep deformation exceeding the permissible limit, with high insitu stress playing a critical role in this phenomenon. To understand the complicated creep behavior of coal, triaxial compression creep tests were conducted. It has been proven that the coal specimens subjected to high confining pressure exhibit typical three-stage creep characteristics. Furthermore, with the increase in confining pressure, the creep threshold value increases while the creep threshold coefficient decreases. By fitting the creep strain-time results, an improved Burgers creep model based on fractional-order was proposed. This model can describe the primary, secondary, and tertiary stages and reflect the nonlinear behavior, contributing to the understanding of the long-term stability evaluation of deep coal pillars.